Consumer Debt in Germany: Status and Development - Sally Peters (Wirtschaftsdienst)
Abstract This article looks at over-indebtedness in Germany and its current status and trends. COVID-19 created increased attention on private debt and over-indebtedness. Various studies within the last two years show the severe financial impact of the pandemic; the situation has only eased in phases, but remains critical overall. A fundamental undersupply of efficient and effective debt counselling has become apparent. Current developments (especially with regard to energy prices) have increased the need for debt counselling.